Effects of Think–Pair–Share on Students’ Achievement and Improvement in Mathematical Understanding of Linear Equations - Merlina Dwi Astuti; Attin Warmi; Haerudin (Jurnal Didactical Mathematics, 2026)
Developing students' mathematical understanding remains a persistent challenge in mathematics education, particularly in learning algebraic concepts such as linear equations, where students frequently rely on procedural knowledge rather than conceptual reasoning. This study investigated the effectiveness of the Think–Pair–Share (TPS) strategy in improving students' mathematical understanding of linear equations compared with conventional instruction. A quasi-experimental nonequivalent pretest–posttest control group design was employed involving 74 eighth-grade students from a public junior high school in Karawang, Indonesia. Participants were selected through purposive sampling and assigned to an experimental group (n = 37) and a control group (n = 37). Mathematical understanding was measured using an essay test developed from the National Council of Teachers of Mathematics (NCTM) indicators, and the data were analyzed using independent-samples t-tests and N-gain analysis. The results indicated no significant difference in students' initial mathematical understanding between the groups (p = .604). Following the intervention, students taught through TPS achieved significantly higher posttest scores than those receiving conventional instruction (58.78 vs. 47.30; p = .026) and demonstrated greater learning improvement, with a moderate N-gain (0.391) compared with the control group's low N-gain (0.242; p = .021). The posttest comparison also yielded a moderate practical effect (Cohen's d = 0.53), indicating that TPS produced educationally meaningful improvements in students' conceptual learning. These findings suggest that TPS provides an effective collaborative learning environment for strengthening students' mathematical understanding of linear equations and supports its implementation as a pedagogical strategy for secondary mathematics instruction.